Cytosolic THUMPD1 promotes breast cancer cells invasion and metastasis via the AKT-GSK3-Snail pathway - Zhang, Xiupeng (Oncotarget, 2017)
Human THUMP domain-containing protein 1 (THUMPD1) is a specific adaptor protein that modulates tRNA acetylation through interaction with NAT10. Immunohistochemical analysis of 146 breast cancer specimens (82 triple-negative and 64 non-triple-negative cases) indicated THUMPD1 expression is higher in breast cancer tissues (60.9%, 89/146) than normal breast tissues (28.3%, 15/53; p < 0.001). Overall and cytosolic, but not nuclear, THUMPD1 expression in breast cancer correlated with advanced TNM stage (p = 0.003 and p < 0.001, respectively), lymph node metastasis (p = 0.001 and p < 0.001, respectively), and poor patient prognosis (p = 0.001 and p < 0.001, respectively). THUMPD1 interacted and co-localized with YAP, but did not affect Hippo pathway activity. THUMPD1 overexpression enhanced breast cancer cells invasion and migration in vivo and in vitro, possibly through activation of AKT, GSK3β and Snail, and inhibition of E-cadherin. Treatment with the AKT inhibitor, LY294002, reduced the effects of THUMPD1 overexpression in breast cancer cells. These results indicate that THUMPD1 promotes breast cancer cells invasion and migration via the AKT-GSK3β-Snail pathway.